Advanced Communication and Networking Second International Conference, ACN 2010, Miyazaki, Japan, June 23-25, 2010. Proceedings - Chang, Chin-Chen.; Vasilakos, Thanos; Das, Purnendu; Kim, Tai-hoon.; Kang, Byeong-Ho.; Khurram Khan, Muhammad; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Advanced Science and Technology, Advanced Communication and Networking, Information Security and Assurance, Ubiquitous Computing and Multimedia Appli- tions are conferences that attract many academic and industry professionals. The goal of these co-located conferences is to bring together researchers from academia and industry as well as practitioners to share ideas, problems and solutions relating to the multifaceted aspects of advanced science and technology, advanced communication and networking, information security and assurance, ubiquitous computing and m- timedia applications. This co-located event included the following conferences: AST 2010 (The second International Conference on Advanced Science and Technology), ACN 2010 (The second International Conference on Advanced Communication and Networking), ISA 2010 (The 4th International Conference on Information Security and Assurance) and UCMA 2010 (The 2010 International Conference on Ubiquitous Computing and Multimedia Applications). We would like to express our gratitude to all of the authors of submitted papers and to all attendees, for their contributions and participation. We believe in the need for continuing this undertaking in the future. We acknowledge the great effort of all the Chairs and the members of advisory boards and Program Committees of the above-listed events, who selected 15% of over 1,000 submissions, following a rigorous peer-review process. Special thanks go to SERSC (Science & Engineering Research Support soCiety) for supporting these - located conferences.
Design of a Reliable Wireless Switch for the Intersection Area on Vehicular Telematics Networks -- A Middleware Based Approach to Dynamically Deploy Location Based Services onto Heterogeneous Mobile Devices Using Bluetooth in Indoor Environment -- Hiding Data in Audio Signal -- Feature Extraction and Analysis of Breast Cancer Specimen -- Three-Phase Scheme for Supporting Time-Constrained Data with Duplication in Wireless Broadcast Systems -- A Feedback-Based Secure Path Approach for Wireless Sensor Networks Data Collection -- An Effective Power Saving Mechanism for IEEE 802.11 PSM in Double-Layered Mobile P2P Systems -- A New Image Enhancement Method Based on Nonsubsampled Contourlet Transform -- Enable Cache Effect on Forwarding Table in Metro-Ethernet -- A Handover Mechanism Using IEEE 802.21 in Heterogeneous Wireless Networks -- Duplicate Address Detection Table in IPv6 Mobile Networks -- A Hop-Sensitive Mechanism to Establish Route Optimization in Mobile Networks -- A Novel Analysis of Single Mode Fiber for Reduction of Chromatic Dispersion Using Dispersion Compensated Fiber -- Image Tampering Detection and Recovery Using Dual Watermarks and Cyclic Redundancy Checks -- Response Time Enhancement of Sensor Network Using the Solid State Drive.
Keywords: Computer science; Computer communication systems; Computer programming; Artificial intelligence; Image processing; Pattern recognition; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Programming Techniques; Pattern Recognition; Image Processing and Computer Vision; Information Systems Applications (incl. Internet).; Electronic books